The Effect of Residential Altitude and Body Mass Index on the Incidence of Hypertension - Khairunnisa, Edgina; Romadhon, Yusuf Alam (Journal La Medihealtico, 2024)
Non-communicable diseases (NCDs) are diseases that are not transmitted from one individual to another, but these diseases develop slowly and have long episodes. One of the most common non-communicable diseases (NCDs) is hypertension. The number of adults aged 30-79 years experiencing hypertension is around 1.28 billion worldwide. The prevalence of hypertension in Indonesia is estimated at 34.1%, showing an increase from 2013 of 25.85%. The prevalence of hypertension in Central Java is the largest case of all non-communicable diseases, which is 76.5%. The prevalence of hypertension in Kendal Regency always increases every year. In 2019 it was around 9.74%, in 2020 it was around 18.21%, and in 2021 it was around 32.32. Objective: This study aims to analyze the effect of residential altitude characteristics and body mass index (BMI) on the incidence of hypertension. This study uses observational analytics with a cross-sectional research design. The sampling technique uses purposive sampling technique. Statistical analysis with univariate analysis using Chi-square and multivariate analysis using logistic regression. Based on the results of the regression model equation show that the probability value ( predicted ) is 0.408. This shows that the sample in this study who have a residence with a residential altitude of 650 meters above sea level ++ and have a BMI with the Overweight/obese category will be predicted to experience hypertension with a predicted value of 0.408. It was found that the characteristics of being left behind are more significant in influencing the incidence of hypertension compared to body mass index, although both are considered risk factors.